Neuromuscular Blockade Depth and Oculocardiac Reflex in Pediatric Strabismus Surgery: A Randomized Clinical Trial - Jung-Bin Park; Jae Ho Jung; Sang-Hwan Ji; Eun-Hee Kim; Ji-Hyun Lee; Jin-Tae Kim; Hee-Soo Kim; Young-Eun Jang (Anesthesiology, 2026)
Background: Although neuromuscular blockade reduces oculocardiac reflex (OCR) incidence compared with no neuromuscular blockade, the effect of blockade depth on OCR has not been prospectively evaluated. This study aimed to evaluate whether the depth of neuromuscular blockade influences the incidence of the OCR during pediatric strabismus surgery. Methods: In this prospective, double-blinded randomized controlled trial, 204 pediatric patients aged 3 to 18 yr undergoing strabismus surgery under general anesthesia were randomly assigned to moderate to deep neuromuscular blockade (MD-NMB; train-of-four count 0 to 3) or minimal to shallow neuromuscular blockade (MS-NMB; train-of-four count of 4 with ratio less than 0.9). The primary outcome was the incidence of OCR grade greater than or equal to 2, defined as a decrease in heart rate from baseline of greater than or equal to 20%. Secondary outcomes included severe OCR (grade of 3 or higher, defined as a decrease in heart rate greater than or equal to 30%), as well as the magnitude and duration of heart rate reduction. Results: A total of 201 patients were analyzed (MS-NMB, n = 102; MD-NMB, n = 99). The incidence of OCR grade of 2 or higher was lower in the MD-NMB group compared with the MS-NMB group (30.3% vs . 53.9%; odds ratio, 0.37; 95% confidence interval [CI], 0.21 to 0.66; P = 0.001). OCR grade of 3 or higher was also reduced in the MD-NMB group (18.2% vs . 35.3%; odds ratio, 0.41; 95% CI, 0.21 to 0.78; P = 0.007). Among patients who developed OCR, the magnitude (34.3% [26.9 to 42.6%] vs . 28.0% [18.2 to 35.9%]; P = 0.003) and duration (46.0 s [30.3 to 65.8 s] vs . 37.0s [17.0 to 49.5 s]; P = 0.024) of heart rate reduction were smaller in the MD-NMB group. Conclusions: Moderate to deep neuromuscular blockade significantly reduced both the incidence and severity of OCR during pediatric strabismus surgery compared with minimal to shallow blockade. These findings suggest that deeper neuromuscular blockade may represent an effective strategy to attenuate OCR during extraocular muscle manipulation.